“In wounded hart”: Spenser’s Faerie Queene and the Emergency of Healing - Andrew Hiscock (Etudes Epistémè)
This article focuses on selected narratives of Spenser’s The Faerie Queene with particular attention to the contexts of illness, healing and convalescence. Discussion explores how Spenser establishes a clear narrative rhythm in his epic poem so that his various protagonists seek refuges for medical and therapeutic intervention at regular points in each of the designated “books” of the work. Of particular interest here are the ways in which Spenser reinterprets Catholic discourses of spiritual failure and healing for a Protestant audience in sixteenth-century England.